2018
DOI: 10.3390/s18093092
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Heart Rate, Respiration and Motion Measurements from a Wearable Sensor System to Enhance Energy Expenditure Estimation

Abstract: This paper presents a new method that integrates heart rate, respiration, and motion information obtained from a wearable sensor system to estimate energy expenditure. The system measures electrocardiography, impedance pneumography, and acceleration from upper and lower limbs. A multilayer perceptron neural network model was developed, evaluated, and compared to two existing methods, with data from 11 subjects (mean age, 27 years, range, 21–65 years) who performed a 3-h protocol including submaximal tests, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Similar findings were shown by Mackintosh et al (2016), who found that two-accelerometer systems had superior accuracy to systems of 3-8 accelerometers when assessing energy expenditure in children. As an alternate to using more accelerometers, using additional sensors alongside an accelerometer (within a single monitor or as a multi-monitor system), such as heart rate or gyroscope, has been shown to improve measurement of energy expenditure and may be considered as an option for further improvement of physical activity intensity assessment (O'Driscoll et al, 2018;Lu et al, 2018;Hibbing et al, 2018).…”
Section: Comparisons Across Demographic Variables For Boosting Methodmentioning
confidence: 99%
“…Similar findings were shown by Mackintosh et al (2016), who found that two-accelerometer systems had superior accuracy to systems of 3-8 accelerometers when assessing energy expenditure in children. As an alternate to using more accelerometers, using additional sensors alongside an accelerometer (within a single monitor or as a multi-monitor system), such as heart rate or gyroscope, has been shown to improve measurement of energy expenditure and may be considered as an option for further improvement of physical activity intensity assessment (O'Driscoll et al, 2018;Lu et al, 2018;Hibbing et al, 2018).…”
Section: Comparisons Across Demographic Variables For Boosting Methodmentioning
confidence: 99%
“…TIP has been used to measure lung volume changes [255], to evaluate respiratory condition during normal and deep breathing [256], the assessment of asthma risk from tidal flow variability [257], sleep disorders [258], energy expenditure estimation [259], or even the detection of body posture changes [260]. Another application of TIP is the gating of positron-emission tomography (PET) and singlephoton emission computed tomography (SPECT) images.…”
Section: Transthoracic Impedance Pneumographymentioning
confidence: 99%
“…The promising results provided by this method showed its capability in characterizing high-dimensional time series patterns and providing useful information with wearable sensors in table tennis coaching. Lu et al [15] developed and tested a new method that combined information from heart rate, respiration, and accelerations measurements to estimate energy expenditure. These data measurements were taken from wearable sensor system and were integrated by neural network based model.…”
Section: Summary Of Special Issue Papersmentioning
confidence: 99%